Beginning XML with CSharp 2008 - Joshi, Bipin (Apress, 2012)
The Internet has brought a huge difference in the way we develop and use software applications. Applications are becoming more and more distributed, connecting heterogeneous systems. With such a radical change, the role of XML is highly significant. XML has already established itself as a standard way of data encoding and transfer. No wonder that Microsoft’s .NET Framework provides such strong support for XML. Data access, raw parsing, configuration, code documentation, and web services are some of the examples where .NET harnesses the power and flexibility of XML. The .NET Framework comes with a plethora of classes that allow you to work with XML data. This book demystifies XML and allied technologies. Reading and writing XML data, using DOM, ADO.NET integration with XML, SQL Server XML features, applying XSLT style sheets, SOAP, web services, and configuration systems are some of the topics that this book explores in detail. Real-world examples scattered throughout the book will help you understand the practical use of the topic under consideration. The book will also act as a handy reference when developers go on the job.